Perbandingan Konverter CUK dan SEPIC Untuk Pelacakan Titik Daya Maksimum Berbasis Panel Surya - Muhammad Syafei Gozali (Politeknik Negeri Batam, 2013)
To meet the increasing demand for electricity, is required the power plants that utilize renewable energy.The rapid development of technology currently, it has been able to take advantage of solar energy into electrical energy by using solar panels.To get the maximum power from the solar panel dc-dc converter is needed, which is controlled by using the maximum power point tracking algorithm(MPPT).This paper presents a comparison between CUK and SEPIC converter in maximum power point tracking of solar panel system. Advantages and disadvantages of both converters are described in this paper. Furthermore, Perturb and Observe (P&O) are used as maximum power point tracking algorithm. The evaluation of the output has been carried out and compared by software simulation.